The effect of vitamin and mineral supplementation on pregnancy rates in kangal sheep during the breeding season - Mehmet Buğra Kıvrak; Abdurrahman Takcı; Bora Bölükbaş; Murat Yüksel (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to determine the effect of parenteral vitamin (?-carotene and vitamin E) and trace element (selenium, manganese, copper, zinc) applications on pregnancy rates in Kangal ewes synchronized during the breeding season. Materials and Methods: The presented study was carried out with 200 Kangal ewe. The animals included in the study were randomly divided into four equal groups. Prostaglandin (PGF-2?) injections were administered to all groups with an interval of 11 days. Before synchronization, a combination of ?-carotene and vitamin E was applied to the one group and a combination of trace elements (selenium, manganese, copper, zinc) to the other group. To determine the effect of these micronutrients, both vitamin and trace elements combinations were applied to the 4th group. In contrast, the 1st group was accepted as the control group, and no treatment was given. Rams were introduced to all groups 48 hours following the last PGF-2? administration. Pregnancy diagnosis was achieved transabdominally by ultrasonography on the 35th and 60th days after ram introduction. Results: Pregnancy rates of control, 2nd, 3rd, and 4th groups at the 35thday examination were 64%, 62%, 50%, and 60%, respectively; pregnancy rates at the 60th-day inspection were 62%, 60%, 50%, and 59%, respectively.. No statistical difference was observed between the control and other groups. Late embryonic death and early fetal death rates were similar between groups. Conclusion: It was concluded that vitamin and mineral supplementation at the beginning of synchronization did not affect fertility, but at least 15 days ago before the onset of synchronization, repeated vitamin and trace element supplementation may increase fertility.